Post-exercise pulse pressure is a better predictor of executive function than pre-exercise pulse pressure in cognitively normal older adults. Issue 4 (3rd July 2016) - Scott, Bonnie M.; Maye, Jacqueline; Jones, Jacob; Thomas, Kelsey; Mangal, Paul C.; Trifilio, Erin; Hass, Chris; Marsiske, Michael; Bowers, Dawn
ABSTRACT: Exercise "stress tests" are widely used to assess cardiovascular function and to detect abnormalities. In line with the view of exercise as a stressor, the present study examined the relationship between cognitive function and cardiovascular activity before and after light physical exercise in a sample of 84 non-demented community-dwelling older adults. Based on known relationships between hypertension, executive function and cerebral white matter changes, we hypothesized that greater post-exercise reactivity, as indexed by higher pulse pressure, would be more related to worse performance on frontal-executive tasks than pre-exercise physiologic measures. All participants were administered a comprehensive neuropsychological battery and underwent a Six Minute Walk Test (6MWT), with blood pressure (BP) measures obtained immediately before and after the walk. Pulse pressure (PP) was derived from BP as an indicator of vascular auto-regulation and composite scores were computed for each cognitive domain assessed. As predicted, worse executive function scores exhibited a stronger relationship with post-exercise PP than pre-exercise PP. Results suggest that PP following system stress in the form of walking may be more reflective of the state of vascular integrity and associated executive dysfunction in older adults than baseline physiologic measures.